Trapping of Transient Thienyllithiums Generated by Deprotonation of 2,3- or 2,5-Dibromothiophene in a Flow Microreactor - Okano, Kentaro; Yamane, Yoshiki; Nagaki, Aiichiro; Mori, Atsunori (Synlett, 2020)
Selective trapping of (4,5-dibromo-2-thienyl)lithium, known to undergo halogen dance, was achieved in a flow microreactor. This transient thienyllithium, generated by mixing 2,3-dibromothiophene and lithium diisopropylamide at –78 °C for 1.6 seconds, reacted with benzaldehyde. The reaction system is also applicable to other carbonyl compounds to afford the corresponding adducts in good yields. Moreover, the established conditions permit the conversion of 2,5-dibromothiophene into a mixture of the two constitutional isomers. The contrasting results are discussed on the basis of the reaction pathway.
Keywords: halogen dance; microreactors; dibromothiophenes; substituent effects; deprotonation; lithiation